2023
DOI: 10.3390/microorganisms11030573
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gut Dysbiosis and the Occurrence of SIBO, LIBO, SIFO and IMO

Abstract: Gut microbiota is the aggregate of all microorganisms in the human digestive system. There are 1014 CFU/mL of such microorganisms in the human body, including bacteria, viruses, fungi, archaea and protozoa. The Firmicutes and Bacteroidetes bacteria phyla comprise 90% of the human gut microbiota. The microbiota support the healthy functioning of the human body by helping with digestion (mainly via short-chain fatty acids and amino acids) and producing short-chain fatty acids. In addition, it exhibits many physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…However, a more specific look at the associations may explain the difference as our data are more granular in that we correlated separately against non-inflammatory and inflammatory lesions, with the finding that Clostridia inversely correlated non-significantly to non-inflammatory lesions (corr: −0.23, p -value: 0.34) but had a stronger correlation with the presence of inflammatory lesions (corr: 0.74, p -value: 0.0001). Furthermore, we noted an association for the presence of inflammatory lesions with Methanobrevibacter smithii , which is a known pathogen associated with gut dysbiosis such as Small Intestinal Bacterial Overgrowth (SIBO) and Intestinal Methanogen Overgrowth (IMO) [ 48 ]. While SIBO has correlated with the scleroderma and rosacea [ 22 , 49 ], our data suggest that further exploration into the association between SIBO and inflammatory acne may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more specific look at the associations may explain the difference as our data are more granular in that we correlated separately against non-inflammatory and inflammatory lesions, with the finding that Clostridia inversely correlated non-significantly to non-inflammatory lesions (corr: −0.23, p -value: 0.34) but had a stronger correlation with the presence of inflammatory lesions (corr: 0.74, p -value: 0.0001). Furthermore, we noted an association for the presence of inflammatory lesions with Methanobrevibacter smithii , which is a known pathogen associated with gut dysbiosis such as Small Intestinal Bacterial Overgrowth (SIBO) and Intestinal Methanogen Overgrowth (IMO) [ 48 ]. While SIBO has correlated with the scleroderma and rosacea [ 22 , 49 ], our data suggest that further exploration into the association between SIBO and inflammatory acne may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The human gastrointestinal (GI) tract harbors trillions of gut microbiota, comprising about 500–1000 different bacterial species, which collectively weigh approximately 1–2 kg [ 1 , 2 ]. Analysis of the human microbial composition has shown that the gut microbiota of adults contains six phyla, with 90% of these bacterial species belonging to the phyla Bacteroidetes and Firmicutes, while the phyla Actinobacteria, Proteobacteria, Fusobacteria, and Verrucomicrobia make up the rest [ 3 ]. The balance of the gut microbiota, namely eubiosis, is important in maintaining health and preventing diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of patients deny effective treatment due to similar clinical phenotypes compared with many other functional gastrointestinal diseases (FGIDs). Few studies provide independent clinical and microbiome profiles of SIBO patients [ 22 ].…”
Section: Introductionmentioning
confidence: 99%